Schemat polemiki z Marcjonem u Ireneusza z Lyonu i Eznika z Kolb - Częsz, Bogdan (Vox Patrum, 1984)
In the present raport I would like to draw attention to two Fathers of the Church - Irenaeus and Eznik of Kolb - whose works contain polemics against Marcion.